A Description and Examination of Fluorescence in Nine North American Firefly Species (Coleoptera: Lampyridae) - Aidan Wilcox (Psyche: A Journal of Entomology)
Fluorescence across the family Lampyridae has been documented sporadically but not comprehensively in formal research. Fireflies (Coleoptera: Lampyridae), best known for their bioluminescence, are also fluorescent. This fluorescence has been documented in several genera within the clade but is still an often overlooked aspect of firefly physiology in the common understanding of the species. To this end, the purpose of this study was to document and describe the fluorescence in nine species of North American fireflies, across three genera. Each species was photographed and a description of the fluorescent pattern was provided, as well as measurements of the specific spectral sensitivity of the fluorescent excitation and emission wavelengths. These data are intended to provide an identification guide of sorts to different firefly fluorescence, as well as documenting definitively its presence in several firefly genera.